Sampling methods for an accurate mycobiota occupational exposure assessment: overview of several ongoing projects - Viegas, Carla (2018)
Exposure to bioaerosols is a critical occupational issue that requires close attention. Workers in several occupational environments, such as health care, agriculture, animal production, waste, fishery, forestry, mining, construction, and daycare are exposed to higher risks of biological hazards due to work characteristics. This review intends to provide information on what is currently known about sampling methods to achieve mycobiota exposure assessment since fungal burden characterization continuous to be a challenging task for every industrial hygienist.